Synthesis and Spectral Properties of Copper(II) Complexes of 4[N-(3'-Nitrobenzyldine) Amino] Antipyrine - Garg, Priyanka; K. Manglik, Ajay; Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
The interaction of 4[N-(3' -nitrobenzylidene) amino] antipyrine (3'-NO2BAAP) with Cu2+ salts in non-aqueous solvent resulted in the coordination complexes with the general composition CuX2·2(3'-NO2BAAP). These complexes were characterized through elemental analyses, electrical conductance, infrared and electronic spectra.